Fabricated And Shia Malay Translated Hadith As Negative Fuzzy Logic Ranking Indicator On Malay Information Retrieval - Shaiful Bakhtiar Rodzman; Sumayyah Hasbullah; Normaly Kamal Ismail; Nurazzah Abd Rahman; Ahmad Yunus Mohd Noor; Zulhilmi Mohamed Nor (The Academy of Sciences Malaysia, 2024)
ASM Sc. J., 13, Special Issue 3, 2020 for CIIDT2018, 100-108